2017
DOI: 10.1038/s41562-017-0069
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a large-scale brain system supporting allostasis and interoception in humans

Abstract: Large-scale intrinsic brain systems have been identified for exteroceptive senses (e.g., sight, hearing, touch). We introduce an analogous system for representing sensations from within the body, called interoception, and demonstrate its relation to regulating peripheral systems in the body, called allostasis. Employing the recently introduced Embodied Predictive Interoception Coding (EPIC) model, we used tract-tracing studies of macaque monkeys, followed by two intrinsic functional magnetic resonance imaging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
299
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 482 publications
(363 citation statements)
references
References 225 publications
7
299
0
Order By: Relevance
“…Interoception refers to the ascending sensory inputs from the organs and systems within the body's internal milieu, which include but are not limited to signals of visceral function and both neuroimmune and neuroendocrine fluctuations (Kleckner et al, 2017). The most recent psychological and neuroscientific studies have shown that the process of interoception is closely associated with emotion, attention, and decision making at both behavioral and brain levels (Barrett, 2017;A.…”
Section: Introductionmentioning
confidence: 99%
“…Interoception refers to the ascending sensory inputs from the organs and systems within the body's internal milieu, which include but are not limited to signals of visceral function and both neuroimmune and neuroendocrine fluctuations (Kleckner et al, 2017). The most recent psychological and neuroscientific studies have shown that the process of interoception is closely associated with emotion, attention, and decision making at both behavioral and brain levels (Barrett, 2017;A.…”
Section: Introductionmentioning
confidence: 99%
“…First, there is the signal processing evidence across species that to enhance efficiency, brains send only the minimum data necessary, as efficiently as possible, and using the least possible neural wiring [1]. 3 Second, there is both structural and functional brain imaging evidence in humans that reveals a system which integrates allostasis and interoception at the core of the brain's intrinsic architecture [52,53] (figure 1). This system consists of two intrinsic networks, conventionally called the default mode network and the salience network, connected by an ensemble of the brain's 'rich club' hubs.…”
Section: Energy Regulation Is At the Core Of The Brain's Computationamentioning
confidence: 99%
“…Prediction errors also arise within the amygdala, the basal ganglia and the cerebellum and are forwarded to the cortex to correct its internal model [52,[103][104][105].…”
Section: Energy Regulation Is At the Core Of The Brain's Computationamentioning
confidence: 99%
See 2 more Smart Citations